Biological activities of Teucrium flavum L., Teucrium fruticans L., and Teucrium siculum rafin crude extracts. (4th July 2018) - Acquaviva, Rosaria; Genovese, Carlo; Amodeo, Andrea; Tomasello, Barbara; Malfa, Giuseppe; Sorrenti, Valeria; Tempera, Gianna; Addamo, Alessandro Paolo; Ragusa, Salvatore; Rosa, Tundis; Menichini, Francesco; Di Giacomo, Claudia
Abstract: The genus Teucrium (Lamiaceae) includes 300 species widespread all around the world, which are perennial herbs or shrubs commonly, named germanders. In Italy, Teucrium flavum L., Teucrium fruticans L., and Teucrium siculum Rafin are mostly present in Liguria, Sicily, and Sardegna. Teucrium species are characterized by mono and sesquiterpene hydrocarbons, flavonoids, fatty acid esters, and essential oils. Many species of this genus show antioxidant, antimicrobial, and antifungal activities, rendering them useful as natural preservative ingredients. In view of the interesting biological properties reported for Teucrium spp., in this study we determined the total phenol and flavonoid content of inflorescence extracts of T. flavum L., T. fruticans L., and T. siculum Rafin. In addition, we investigated the in vitro antioxidant and antibacterial activities of inflorescence extracts against pathogenic bacteria. Obtained results demonstrated that extracts had in vitro antioxidant activity and showed antimicrobial ability against Gram-positive and Gram-negative strains albeit with different effectiveness probably due to the different qualitative/quantitative composition of the extract also suggesting that these extracts might be useful in preventing several diseases in which oxidative stress may represent an important pathogenic mechanism.